Remote Electrical Parameters Measurement Using The Blynk Aplication - Setiyono Setiyono (Fakultas Teknik, 2022)
The recording of the amount of electrical energy consumed by the public on postpaid electricity customers often experiences reading errors by officers. The contributing factor is the absence of occupants of the house when recording the amount of power used by the officer so that the officer records the use of electrical power based on the average previous use. Therefore, to find out the amount of electrical energy that is being used, a periodic electrical energy monitoring system is needed. This device is designed to support monitoring the use of electrical energy in household consumers. Arduino uno as a microcontroller based atmega28, current sensor and voltage sensor are supporting devices used as a monitoring system for the use of electrical energy that can provide information on electrical parameters such as voltage, current, power values, using the blynk application by utilizing the development of Internet of Think technology. IoT) so that the use of electrical power can be seen anytime and anywhere via the internet network. This tool has an average reading error value of 13.68% for current and 14.06% for power. Based on these data, this system is very suitable to be used as a monitoring of electric power consumption because the error generated is quite small.